Clinical effect of lymphocyte immunotherapy on patients with unexplained recurrent spontaneous abortion - Sudong Liu; Xiaodong Gu; Ruiqiang Weng (Immunity, Inflammation and Disease, 2021)
Abstract Introduction Lymphocyte immunotherapy (LIT) is believed to be a viable treatment for unexplained recurrent spontaneous abortion (URSA), but its effect remains controversial. This study aims to investigate the clinical effect of LIT in patients with URSA and clarify the factors that may influence the outcome of LIT. Methods This study included a total of 704 URSA patients, of which 444 patients accepted LIT treatment. URSA patients that did not accept LIT served as control group. Clinical characteristics were collected and analyzed between LIT and control group. The blocking antibody was tested before and after LIT. The outcome of LIT treatment was recorded. Logistic regression analysis was applied to evaluate the independent predictors of LIT success. Results After LIT treatment, 77.9% (346/444) of USRA patients turned to BA positive, and the conversion rate elevated with increased LIT (p < .001). LIT significantly improved the pregnancy rate and live birth rate in USRA patients (65.3% vs. 29.6%, p < .001; 80.3% vs. 50.6%, p < .001). Multivariate regression analysis suggested that younger maternal age and positive BA were independent predictors of LIT success. Conclusion LIT effectively induced the production of BA, and improved pregnancy rate and live birth rate in URSA patients. Our findings supported LIT as a beneficial treatment for URSA.